Application and standardized management of projection infrared vein finder in peripheral venipuncture (投影式红外血管成像仪在外周静脉穿刺中的应用及标准化管理探讨) - E Haiyan (鄂海燕); TANG Ling (唐玲); SUN Lei (孙磊); WANG Yali (王亚丽); ZHI Hui (智慧); WANG Huaxin (王华新); LIU Jinjing (刘津京) (Association of Integrative Nursing, 2021)
The continuous innovation in the medical technology sector is helping to the application of infrared vein finder in peripheral venipuncture. This paper summarized the factors causing peripheral venipuncture failure in the clinical setting and principles of vascular visualization technology, briefly introduce the application process of infrared vein finder in peripheral venipuncture, and discuss related standardized management procedure. (随着医疗技术的不断进步, 血管成像仪逐渐被应用于外周静脉穿刺操作中。本文初步总结了临床外周静脉穿刺失败的原因, 阐述血管可视化技术的原理, 简要介绍了外周静脉穿刺中投影式血管成像仪的应用流程, 并探讨血管成像可视化系统的应用标准。)